Konflik Korupsi akan berpengaruh pada Budaya Organisasi yang Buruk - Darwis Dahlan; Muhammad Fadil Prakoso; Sentot Imam Wahjono (Journal of Innovative and Creativity, 2025)
Corruption remains a significant concern in Indonesia due to its extensive impact on government stability, public trust, and national economic performance. Although Indonesia's Corruption Perception Index (CPI) score improved in 2024, its global ranking still reflects substantial challenges in upholding integrity. This research employs a literature review method to analyze the causes and impacts of corruption as well as the effectiveness of anti-corruption policies such as Good Corporate Governance (GCG), gratuity control systems, and Whistleblowing Systems (WBS). The findings reveal that the root of corruption in Indonesia lies not only in weak oversight and policies but also in organizational cultures that tolerate corrupt practices. Therefore, transforming organizational culture and enforcing ethical values are crucial to establishing a transparent, accountable, and high-integrity work environment. This study recommends improving organizational culture, consistently enforcing codes of ethics, and strengthening the legal culture as comprehensive strategies to reduce corruption and enhance the nation's competitiveness.